Marathi WordNet Development (International Journal of Engineering and Computer Science, 2014)
WordNet is a dictionary of word meanings/concepts. Hence there must be a standard representation of the concepts in order to simulate a lexical matrix on a machine. Marathi is an Indo-Aryan language spoken by about 71 million people mainly in the Indian state of Maharashtra and neighboring states. In WordNet, which is basically a semantic network, the different lexical categories of words (nouns, verbs,..) are organized into 'Synsets' (sets of synonyms). Each synset represents a lexical concept and they can be linked by different types of relation (Hypernymy, antonym, etc.).  The WordNet for Marathi 36842 unique words grouped in more than 26988 Synsets, linked synset 24398 [1]. We would like to increase unique words, with that we want to give special efforts on wards which are oriented towards Marathi culture only for example  culture aspects of words like that  Lawani, Abhang, Fugaddi, Ringan etc.